The interconnection of literacy in history, law, and politics with public trust in the government - Dyah Estyani Cahya; Muhammad Afrillyan Dwi Syahputra; Olin Monalvia (Priviet Social Sciences Journal, 2025)
Public trust in the government does not emerge suddenly; rather, it is shaped by the public’s understanding of social and state dynamics. Historical, legal, and political literacy are important elements that influence citizens’ assessment of government policies and performance. Individuals with low literacy levels tend to respond passively to social and political issues, often accepting government actions without critically evaluating them. This study aimed to analyze the relationship between historical, legal, and political literacy and the level of public trust in the government. A quantitative approach was employed using a survey method, with sample selection carried out through quota sampling to ensure respondent representation across specific categories. The collected data were analyzed using Kendall’s Tau-b correlation test to measure the strength and direction of the relationship between variables. The results of the analysis indicate that there is no significant correlation between historical, legal, or political literacy and public trust in the government (Sig. > 0.05). The low correlation coefficient suggests that these three forms of literacy do not directly influence public trust. These findings indicate that literacy plays a greater role in shaping individuals’ critical awareness and reflective ability to evaluate government performance, rather than simply increasing passive trust.